2023
DOI: 10.3389/ffgc.2022.1072661
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress and recovery effects on the physiology and biochemistry of Castanea sativa Mill.

Abstract: Chestnut forests are undergoing increasing heat stress due to the current global warming, but little is known about the physiology and biochemistry responses of Castanea sativa Mill. to heat or whether differences exist between populations. Six-month-old seedlings from three climatically contrasting populations of C. sativa (from the north, centre, and south of Spain) were subjected to control and heat stress conditions for 7 days. The effects of heat stress on seedlings and their recovery (10 days after heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
6
0
1
Order By: Relevance
“…Similarly, in Quercus suber seedlings exposed to low temperatures, a higher concentration of flavonoids was reported compared to control plants, suggesting that the biosynthesis of these compounds was encouraged by low temperatures [ 60 ]. In similar aged C. sativa seedlings subjected to heat stress, an increase in phenolic compounds was observed in roots [ 28 ], although the response varied depending on the tree origin. In trees, the biosynthesis of secondary metabolites in response to heat appears to be species- and compound-dependent [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in Quercus suber seedlings exposed to low temperatures, a higher concentration of flavonoids was reported compared to control plants, suggesting that the biosynthesis of these compounds was encouraged by low temperatures [ 60 ]. In similar aged C. sativa seedlings subjected to heat stress, an increase in phenolic compounds was observed in roots [ 28 ], although the response varied depending on the tree origin. In trees, the biosynthesis of secondary metabolites in response to heat appears to be species- and compound-dependent [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed changes or shifts in trends in phenolic content occur when plants have entered a recovery phase after stress [ 57 , 59 , 61 , 62 ]. During the recovery phase, plants tend to restore phenolic content to ambient temperature levels, unless physiological damage occurs [ 28 , 63 ]. The increase in several phenolic compounds in our heat-wave-stressed plants may have occurred as a consequence of stress memory, as observed for Alopecurus pratensis [ 62 ], but this needs further study to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in the Earth’s meteorological parameters are alarming consequences of climate change . These changes are the results of the intensification of greenhouse gas emissions . Furthermore, global warming has already reached 1.1 °C in recent years compared to the preindustrial era, and its impact on ecosystems is more severe than estimated in previous reports.…”
Section: Introductionmentioning
confidence: 95%
“…In the other hand heating stress also affects plant growth, development (Dorado et al, 2023), oxidative status , water balance (Dinler et al, 2023), protein folding (Yadav et al, 2020) etc. heating causes physiological wilting in plants, which forces plants to respond with solute accumulations (Parrotta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%